On the Feedback Solution of a Differential Oligopoly Game with Hyperbolic Demand and Capacity Accumulation - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
I characterise the subgame perfect equilibrium of a differential market game with hyperbolic demand where firms are quantity-setters and accumulate capacity over time à la Ramsey. I show that the open-loop solution is subgame perfect. Then, I analyse the feasibility of horizontal mergers, and compare the result generated by the dynamic setup with the merger incentive associated with the static model. It appears that allowing for the role of time makes mergers more likely to occur than they would on the basis of the static setting.
Keywords: C73; L13; 330